How effective are drainage systems in mitigating flood losses?. (December 2020) - Sohn, Wonmin; Brody, Samuel D.; Kim, Jun-Hyun; Li, Ming-Han
Abstract: The impacts of flooding can be devastating. Huge financial burden often follows major storm events to recover from structural damage. Well-designed drainage systems allow for effective discharge of stormwater, reducing property losses and expenditures on recovery. However, a lack of empirical studies on the topic has impeded the determination of which drainage method might be the most effective in preventing or minimizing property losses from flooding. This study assessed the economic impacts of three drainage systems − storage-, conveyance-, and infiltration-based facilities – on reducing flood damage recorded from 2009 to 2012 by Federal Emergency Management Agency in the Buffalo Bayou watershed in Houston, Texas, USA. Ordinary least squares and spatial autoregressive models were developed with a group of variables featuring drainage system, housing structure, geophysical environment, and storm characteristics. The results show that storage-based systems outperform conveyance-based mechanisms. Infiltration-based facilities are found to be less effective in reducing property damage because green spaces disconnected from sewer systems are rapidly inundated after being saturated while excessive overflow is not properly drained. This study confirms that the performance of a drainage system varies by facility type and environmental setting. The results encourage the recovery of wetlands and integration of retention/detention basins into community development in flood-prone areas to prevent potential future economic losses. Highlights: Storage-based drainage mechanisms are most effective for flood mitigation. 92% of flood damage cost can be saved by using storage-based facilities. Installing conveyance-based systems on property roads reduces flood damage by 19%. Directing runoff to green spaces causes undesirable effects on property losses.